The Development of a Strategic Leadership Model for Teacher Instructional Competencies at the Private Higher Education Institutions in Mindanao, Philippines - Estudillo, Haide Mallorca; Mhunpiew, Nathara (Scholar: Human Sciences, 2021)
The purpose of the study was to develop a strategic leadership model for teacher instructional competencies at the private higher education institutions in Mindanao, Philippines. To achieve the six objectives of the study, the researcher employed the exploratory mixed-method research design by collecting substantial qualitative data from sources such as books, journals, online sources, and an interview. While the quantitative research design by collecting data using the survey questionnaire. There were 229 teachers and seven school leaders from private higher education institutions in Mindanao, Philippines, who participated in the study. Frequency counts, Percentage, Mean, Standard Deviation, Pearson’s Correlation Coefficient, and Multiple Regression were used to analyze quantitative data, while a content (thematic) analysis used for qualitative data or interviews. The findings of the current strategic leadership practices of school leaders, as perceived by teachers are interpreted as high. Teachers find the Instructional Practices of the school leaders as high, while school leaders revealed most of their strategic leadership practices focused on Human Resource Management Practice. The current instructional competencies, as perceived by teachers, are interpreted as high. Among the three themes, teachers find their Personal Competence as high. While school leaders give priority to the development of teachers’ Professional Competence. The seven factors affecting the strategic leadership practices of school leaders perceived by teachers as high. The top three factors include Organizational Culture, Organizational Values, and Leadership Competence. While, in the interview with school leaders, essential factors affecting strategic leadership practices include Resource Allocation, Teacher Satisfaction, and Teacher Commitment. A substantial positive relationship revealed between strategic leadership practices and teachers’ instructional competencies of private higher education institutions. The researcher developed the strategic leadership model for teacher instructional competencies and validated by 12 experts. The model comprises of two major levels derived from the Multiple Regression test results as Leadership Competence with a p-value of 0.000 and Organizational Values with a p-value of 0.014 as significant factors.